Direct to angiography suite approaches for the triage of suspected acute stroke patients: a systematic review and meta-analysis - Brehm, Alex; Tsogkas, Ioannis; Ospel, Johanna M.; Appenzeller-Herzog, Christian; Aoki, Junya; Kimura, Kazumi; Pfaff, Johannes A.R.; Möhlenbruch, Markus Alfred; Requena, Manuel; Ribo, Marc J.; Sarraj, Amrou; Spiotta, Alejandro M.; et al. (Therapeutic advances in neurological disorders, 2022)
Background:Increasing evidence suggests improved time metrics leading to better clinical outcomes when stroke patients with suspected large vessel occlusion (LVO) are transferred directly to the angiography suite (DTAS) compared with cross-sectional imaging followed by transfer to the angiography suite. We performed a systematic review and meta-analysis on the efficacy and safety of DTAS approaches.Methods:We searched Embase, Medline, Scopus, and clinicaltrials.gov for studies comparing outcomes of DTAS and conventional triage. Eligible studies were assessed for risk of bias. We performed a random-effects meta-analysis on the differences of median door-to-groin and door-to-reperfusion times between intervention and control group. Secondary outcomes included good outcome at 90?days (modified Rankin Scale???2) rate of symptomatic intracranial hemorrhage (sICH) and mortality within 90?days.Results:Eight studies (one randomized, one cluster-randomized trial and six observational studies) with 1938 patients were included. Door-to-groin and door-to-reperfusion times in the intervention group were on median 29.0?min [95% confidence interval (CI): 14.3?43.6; p?
Article first published online: March 2, 2022
Gesehen am 02.06.2022